Neonatal stunting and early childhood caries: A mini-review - Setiawan, Arlette Suzy; Indriyanti, Ratna; Suryanti, Netty; Rahayuwati, Laili; Juniarti, Neti (Frontiers in Pediatrics, 2022)
The nutritional status of pregnant women greatly determines their newborn outcome. Deficiencies of several micronutrients are associated with stunting in early childhood, affecting health into adulthood. However, apart from the systemic disease that has been a concern so far, fetal undernutrition can also be associated with dental caries in a child's early life, especially since the primary teeth begin to form during the mother's gestation period. The important thing to underline regarding the intrauterine formation of primary teeth is especially in terms of enamel formation. One of the causes of developmental enamel defects that will contribute to the emergence of early childhood caries is the malnutrition of the pregnant mother. This mini-review aims to understand the linkage mechanism behind neonatal stunting to early childhood caries. This concept is expected to generate further research to help prevent both growth stunting and early childhood caries. In addition, with some evidence-based research, the importance of the first dental visit can be further promoted.